Designing an EAP Course to improve Analytical Writing Proficiency of Graduate Level ESL Learners in the Digital Age - Shakil, Ezzah; Siddiq, Sadaf (Annals of Human and Social Sciences, 2024)
This study aims to design an EAP analytical writing course for ESL learners studying at graduate level. In the age of digitalisation, ESL learners tend to rely blindly on internet material for the accomplishment of their academic writing tasks. This malpractice has posed serious threat to their critical thinking skills, analytical writing proficiency, and argumentative discourse. The design of the study is explanatory sequential mixed method involving theory triangulation at its various stages. In order to design the course, needs analysis was conducted, in the first phase, by using a closed-ended questionnaire consisting of 15 items. Convenience sample of 100 ESL learners studying at the Islamia University of Bahawalpur was selected. The statistical data of the study led to second phase of the study i.e. the qualitative phase. This research is situated within the footsteps of multifarious theoretical frameworks. Framework proposed by Dudley-Evans and St. John (1998) guided the questionnaire items. The principles of EAP course design proposed by Klimova (2015) and Brown (1995) were followed. However, the overall foundations of the study were informed by main tenets of “A Test of the Shallowing Hypothesis” by Annisette and Lafreniere (2017). The study recommends the implementation of the proposed EAP course, including its syllabus design, objectives, assessment, and evaluation criteria, for the improvement of analytical writing proficiency of ESL learners in digital age.